The art of gathering eaudiobook How we meet and why it matters. - Parker, Priya (Penguin Audio, 2018)
"Hosts of all kinds, this is a must-read!" —Chris Anderson, owner and curator of TED   From the host of the New York Times podcast  Together Apart , an exciting new approach to how we gather that will transform the ways we spend our time together—at home, at work, in our communities, and beyond. In  The Art of Gathering , Priya Parker argues that the gatherings in our lives are lackluster and unproductive—which they don't have to be. We rely too much on routine and the conventions of gatherings when we should focus on distinctiveness and the people involved. At a time when coming together is more important than ever, Parker sets forth a human-centered approach to gathering that will help everyone create meaningful, memorable experiences, large and small, for work and for play. Drawing on her expertise as a facilitator of high-powered gatherings around the world, Parker takes us inside events of all kinds to show what works, what doesn't, and why. She investigates a wide array of gatherings—conferences, meetings, a courtroom, a flash-mob party, an Arab-Israeli summer camp—and explains how simple, specific changes can invigorate any group experience. The result is a book that's both journey and guide, full of exciting ideas with real-world applications.  The Art of Gathering  will forever alter the way you look at your next meeting, industry conference, dinner party, and backyard barbecue—and how you host and attend them.